Riding the innovation wave : learning to create value from ideas - Bessant, J. R. (Emerald Publishing Limited, 2017)
Innovation matters - being able to create value from ideas is crucial to survival and growth. But while any organization might get lucky once being able to repeat the trick requires learning and developing particular ways of working which enable the process. Over a hundred years of research and practical experience now provides a knowledge base from which we can draw to help develop such approaches. But how do we move from prescription to implementation? And how does the innovation challenge play out over the lifetime of an organization? How does it renew its capability to innovate and do so against a background of dramatically changing markets, technologies and social trends? This book draws on a detailed history of a large German company (HELLA ), now active in over 35 countries, employing 34,000 people. It didn't start out that way, it began as an entrepreneurial start-up in the late 19th century in the (then) uncertain early days of the car industry. It moved from selling whips and other buggy accessories for horse-drawn carriages to horns and lamps for the new-fangled motor cars beginning to appear on the roads of north-western Germany. The journey since then has been one of innovation - in products and processes, in entering new markets, in adding services to its products, and in changing its underlying business models. Survival for over a hundred years is not an accident - it has been built on learning how to innovate and on constantly challenging and updating those models.- Resumé vydavatel
Obsahuje index.
Keywords: HELLA -- dějiny; úspěch v podnikání; kreativita; podnikání; strategický management; organizační změna; success in business; creative ability; business; strategic planning; organizational change; monografie; elektronické knihy; monographs; electronic books